Motywacja nauczycieli do pracy w kontekście awansu zawodowego na przykładzie Szkoły Podstawowej w Roztoce-Brzezinach oraz Zespole Szkól w Rożnowie - Konopka, Magdalena (My University, 2012)
Niniejsza praca porusza kwestię motywacji nauczycieli do pracy w kontekście awansu zawodowego. W wyniku reformy oświaty w Polsce, która nastąpiła w 1999 r. stworzono szczeble awansu, w którym można uzyskać następujące stopnie: nauczyciela stażysty, nauczyciela kontraktowego, nauczyciela mianowanego oraz nauczyciela dyplomowanego. Awans pobudził nauczycieli do intensywniejszej pracy a także spowodował wzrost ich płac. Badania zawarte w pracy zostały przeprowadzone w Szkole Podstawowej w Roztoce – Brzezinach oraz w Zespole Szkół w Rożnowie. Obie szkoły znajdują się na terenie gminy Gródek n/Dunajcem. W badaniu uczestniczyło 25 nauczycieli. Do tego celu użyto ankiety zawierające 18 pytań zamkniętych. Rezultatem przeprowadzonych badań jest potwierdzenie kwestii, że awans zawodowy motywuje nauczycieli do pracy. Odczuwają oni potrzebę podnoszenia swoich kwalifikacji zawodowych oraz większość z nich uważa się za osoby zmotywowane do pracy. Za jeden z głównych i pozytywnych aspektów awansu wskazują także wzrost wynagrodzenia, które jest dla nich satysfakcjonujące. Przeprowadzenie reformy, w której nauczyciel w trakcie swojej kariery zawodowej, zdobywa kolejne szczeble awansu zawodowego, spotyka się z pozytywną reakcją wśród ankietowanych nauczycieli.

The following piece of academic writing concerns the aspect of teachers’ motivation to work on the basis of proffesional advancement. Levels of educational advancement have been set due to an educational reform that took place in Poland back in 1999. As a result a teacher can acquire the following levels of advancement: a probational teacher, a contractual teacher, a designate teacher and finally a graduate teacher. The aspect of promotion itselt has triggered the mechanism of teachers’ motivation to work and what is obvious, it has also raised their salaries. The research has been carried out in two state schools – an Elementary School in Roztoka- Brzeziny and a Middle School in Rożnów. Both schools are located in the parish of Gródek nad Dunajcem. Twenty-five teachers have filled in the survey, which consisted of eighteen closed-end questions. The results of the survey unambiguously show that the teachers’ professional advancement carries a work motivational aspect. Most of the teachers, who acquire the levels of educational advancement claim that they are motivated to work and what is more teachers as general feel the need to get better qualifications. One of the main and positive features of the professional advancement is their salary growth, which is obviously satisfying for the teachers. The execution of the educational reform, thanks to which the teachers can acquire particular levels of their professional development has been met with positive reactions among the interviewee teachers.
Teachers' Motivation in the Context of Professional Advancement on the Example of Elementary School in Roztoka-Brzeziny and School in Rożnów
Keywords: motywacja; struktura oświaty; reforma oświaty; nauczyciele; awans zawodowy nauczycieli; ankieta; motivation; structure of education; educational reform; teachers; teachers’ professional advancement; survey